Rediscovery of the Type Specimens of the Sarcopterygian Fishes Onychodus sigmoides and Onychodus hopkinsi from the Devonian of Ohio, USA - Loren E. Babcock (Diversity, 2025)
John Strong Newberry described three species of the lobe-fin fish Onychodus (Osteichthyes, Sarcopterygii, Onychodontida) based on parasymphysial teeth, or tusks. Two species, Onychodus sigmoides Newberry, 1857 (type species of the genus) and Onychodus hopkinsi Newberry, 1857, were described from the “fish beds” in the Delaware Limestone (Middle Devonian, Eifelian) of Delaware, Ohio, USA; and one species, Onychodus ortoni Newberry, 1889, was described from the Ohio Shale, Huron Member (Upper Devonian, Famennian) of Perry Township, Franklin County, Ohio. In 1873, Newberry replaced the original species-group definition of O. hopkinsi with a definition based on teeth of different morphology from the West Falls Group (Upper Devonian, Frasnian) of Franklin, New York. Specimens of Newberry’s original Onychodus material, including the primary types, which were long assumed to be lost, have been rediscovered in a 19th-century collection. They show O. hopkinsi to be a junior synonym of O. sigmoides and clarify the species definition of O. sigmoides. Onychodus sigmoides, which is recognized from Middle Devonian strata of the Appalachian Basin in the United States and Canada, shows two end-member shapes of teeth on the parasymphysial whorl: procurved (arcuate) or nearly so proximally and recurved distally (anteriorly). Small teeth are commonly more slender than large teeth, which are robust. Parasymphysial teeth from the Upper Devonian of Ohio and New York are referred to O. ortoni.